Tracking the Subtle Mutations Driving Host Sensing by the Plant Pathogen Streptomyces scabies - Samuel Jourdan (American Society for Microbiology, 2017)
ABSTRACT The acquisition of genetic material conferring the arsenal necessary for host virulence is a prerequisite on the path to becoming a plant pathogen. More subtle mutations are also required for the perception of cues signifying the presence of the target host and optimal conditions for colonization. The decision to activate the pathogenic lifestyle is not “taken lightly” and involves efficient systems monitoring environmental conditions. But how can a pathogen trigger the expression of virulence genes in a timely manner if the main signal inducing its pathogenic behavior originates from cellulose, the most abundant polysaccharide on earth? This situation is encountered by Streptomyces scabies, which is responsible for common scab disease on tuber and root crops. We propose here a series of hypotheses of how S. scabies could optimally distinguish whether cello-oligosaccharides originate from decomposing lignocellulose (nutrient sources, saprophyte) or, instead, emanate from living and expanding plant tissue (virulence signals, pathogen) and accordingly adapt its physiological response.